«Tu, solo, con la storia alle spalle». Durs Grünbein e la DDR: un bilancio critico (Studia theodisca, 2011)
This paper analyses some of the most significant (post-)GDR poems by Grünbein and traces the development of aesthetic and poetological issues that are central to the poet’s oeuvre. It provides an articulated overview of Grünbein’s poetics by examining fundamental themes like the love/hate attitude towards his hometown Dresden, the complementary concepts of history and memory, and the materialism of the body as an antidote to utopias.